South Africa : Financial Sector Assessment Program-Technical Note on Cybersecurity Risk Supervision and Oversight. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2022)
Cybersecurity risk continues to grow both in complexity and severity and is a function of an increasingly open and interconnected cyber and financial ecosystem. The South African financial system has a long history of incorporating technology and as for many financial systems across the globe, digitalization has become a strategic priority. For risk management to keep pace with the dynamic nature of cyber threats and threat agents, systemically important financial institutions (SIFIs) have made substantial investments in cyber resilience programs (e.g., establishing cyber strategies, frameworks, and governance structures). Consistent with many jurisdictions, and partly a result of widespread remote working arrangements implemented in response to the global pandemic, cybersecurity threats to financial stability increased. However, high standards of risk management meant threats did not materialize into significant losses and/or disruptions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; South Africa